(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Vovk N. V. The features of the structural elements of consumer culture forming of the future teachers of technology. The concept of the analysis of «consumption» is presented in the article as well as the essence of the concept «consumer culture», «culture of consumption» is analysed, components of the consumer culture are defined. The culture of consumption of the future teacher has dynamic development that is carried out on the basis of satisfaction of needs in professional activity, culture, personal values. The consumer’s culture gives examples of models of consumption, elections, values and tastes which help the person to be guided in the social space and to get a high quality education.